Odpowiedzi

2010-01-20T17:07:57+01:00
3x-2(x+1)+3+3x
3x-2x-2+3+3x
4x+1

5(x-1)+2x=2(x+1)+8
5x-5+2x=2x+2+8
5x=5/5
x=1

2(4-x)=5(x-1)-1
8-2x=5x-5-1
-7x=-14/-7
x=2

2010-01-20T17:12:36+01:00
A)
3x-2(x+1)+3+3x=3x-2x-2+3+3x= 4x +5
tylko tu nie wiadomo, gdzie jest znak =
b)
5(x-1)+2x=2(x+1)+8
5x-5+2x =2x+2+8
5x+2x-2x=2+8+5
5x=15
x=15:5
x=3
spr.
L=5(x-1)+2x= 5(3-1)+2*3=5*2+6=10+6=16
P=2(x+1)+8=2(3+1)+8= 2*4+8=8+8=16
L=P
c)
2(4-x)=5(x-1)-1
8-2x=5x-5-1
-2x-5x= -5-1-8
-7x= -14
x= (-14) :(-7)
x=2
spr.
L=2(4-x)= 2(4-2)=2*2=4
P=5(x-1)-1 =5(2-1)-1= 5*1-1=5-1=4
L=P
2010-01-20T17:16:49+01:00
5(x-1)+2x=2(x+1)+8
5x-5+2x=2x+2+8
5x+2x-2x=2+8+5
5x=15/:5
x=3
spr.
5(3-1)+2*3=2(3+1)+8
5*2+6=2*4+8
10+6=8+8
16=16

2(4-x)=5(x-1)-1
8-2x=5x-5-1
-2x-5x=-5-1-8
-7x=-14/-7
x=2
spr.
2(4-2)=5(2-1)-1
2*2=5-1
4=4

3x-2(x+1)+3+3x
3x-2x-2+3+3x
4x=-4/:4
x=-1